The Effect of Occupational Licensing Deregulation on Migrants in the German Skilled Crafts Sector - Petrik Runst (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2016)
Occupational Licensing may reduce the entry of minorities, such as migrants, into a profession if the likelihood of fulfilling the licensing requirements is lower in this group. While policy makers typically justify occupational licensing on the grounds of quality control it, thus, also has the potential to adversely affect the labor market integration of foreign-born citizens. Before the backdrop of increased levels of migration into Germany, and the general discussion about the free movement of labor in Europe, this paper empirically examines the effects of the deregulation of occupational licensing in the German crafts sector on the proportion of migrants working in this sector. The results suggest that the reform has increased the proportion of migrants by about 5 percentage points among self-employed professionals and 6 percentage points among employed craftsmen.
Keywords: D45; K20; L51; 330; Occupational Licensing; Migrants; Germany; Crafts